Bandit Nation : A History of Outlaws and Cultural Struggle in Mexico, 1810-1920 - Frazer, Chris, 1959- (Book collections on Project MUSE., 2006)
"Bandit Nation is the first complete analysis of the cultural impact that banditry had on Mexico from the time of its independence to the Mexican Revolution. Chris Frazer focuses on the nature and role of foreign travel accounts, novels, and popular ballads, known as corridos, to analyze how and why Mexicans and Anglo-Saxon travelers created and used images of banditry to influence state formation, hegemony, and national identity. Narratives about banditry are linked to a social and political debate about "mexican-ness" and the nature of justice."--pub. desc.